Knowledge and Perceptions of Human Rights among University Students in Puerto Rico - Yudkin Suliveres, Anita (2025)
This article presents the key findings of a study on the knowledge and perceptions of human rights among first-year students at the University of Puerto Rico, Río Piedras campus. This mixed-methods research comprised two phases: a quantitative survey and qualitative focus group discussions. The investigation indicates that the students had varied higher education experiences regarding exposure to human rights education. Moreover, they have limited formal knowledge of these rights, though they are well-acquainted with human rights principles. The students identify the country's situation as a violation of this matter, particularly in relation to the events that unfolded after 2016. They express a willingness to recognize, defend, and advocate for both their own rights and the rights of others. They place significant importance on the right to education and the necessity of human rights education at both the school and university levels. They advocate for relevant and dynamic instruction in these rights, incorporating social networks and information technologies.